Polysaccharides from Bletilla striata protect against mercury-induced gastrointestinal toxicology in adult Drosophila melanogaster via modulation of sestrin - Zhi Chen; Fen Wang; Wen Zhang; Shuangshuang Zhou; Di Wen; Ren Mu (Ecotoxicology and Environmental Safety, 2023)
Oxidative stress was one of the major causes of heavy metal-induced toxicity in organisms. The polysaccharide from Bletilla striata (Orchidaceae) (BSP) has been recently recognized as a novel player in the management of oxidative stress response in organisms. Here, we took the midgut of adult Drosophila melanogaster (Diptera: Drosophilidae) (D. melanogaster), a functional equivalent to the mammalian intestine and stomach, as a model to evaluate the protective effects of BSP (50 μg/mL) on mercuric chloride-induced gastrointestinal toxicology in insects. As a result, BSP exposure significantly improved the survival rates and climbing ability of adult flies exposed to mercury. Further study demonstrated that BSP significantly alleviated the mercury-induced oxidative injury to midgut epithelium, at least partly, through increasing antioxidant enzyme activity (glutathione-S-transferase and superoxide dismutase), decreasing reactive oxidative species production, inhibiting cell death, restoring intestinal epithelial barrier and regulating intestinal stem cell-mediated tissue regeneration. Additionally, sestrin, an oxidative-stress gene, was required in mediating the protection of BSP against mercury-induced oxidative damage to midgut. This study suggested that BSP has great potential for future application in the treatment and prevention of heavy metal-induced gastrointestinal adversities in mammals.